Technical and tactical analysis of high level kickboxing matches - Ouergui, I.; Hssin, N.; Franchini, E.; Gmada, N.; Bouhlel, E. (International Journal of Performance Analysis in Sport, 2013)
The purpose of the study was to analyze the technical and tactical aspects of high level Kickboxing matches. A total of 45 matches (135 rounds) from the World Championship 2009 and 2011 of male kickboxers were analyzed using notational analysis system to determine the technical and tactical aspects (i.e., offensive, defensive techniques and combined actions) considering combat rounds, weight divisions and match outcome. Kickboxers were engaged in offensive actions more than defensive ones (P<0.001). The most used techniques were straight punches, roundhouse kick, block/parry and foot defense (P<0.001), while punch combinations were the most used combination type. Winners used more offensive (i.e., hook punches), defensive techniques (i.e., foot defense and clinch) and punch combinations than losers. Significant interation effect of weight category, match outcome and rounds were found on offensive and defensive techniques. The activity in international kickboxing competitions was modulated by weight categories with a significant effect of combat stage. Winners applied more offensives and defensives techniques than defeated athletes. Our findings suggest that to win a match, athletes should be motivated by developing the most used offensives techniques and coaches should structure specific training to maintain a high rate of techniques 'delivery during the combat.